Antioxidant Activity and Reactive Oxygen Species (ROS) Scavenging Mechanism of Eriodictyon californium, an Edible Herb of North America - Allie Richards; Savita Chaurasia (Journal of Chemistry)
Modern life associated with processed food, exposure to a wide range of pollutants, physical inactivity, unprecedented time, excessive involvement of technology in our lives, and so on give rise to oxidative stress which threatens our physical and mental health. Because of rising healthcare costs and mistrust of conventional medicine, mankind is looking for alternatives to over-the-counter medications and prescription drugs, which is driving the demand for nutraceuticals across the globe. Antioxidant-rich plant-based natural products could be an important source of nutraceuticals to boost endogenous antioxidant levels. In this research, we uncovered the antioxidant potential of Eriodictyon californicum, an herb used by Native Americans for centuries to treat a wide range of ailments. The ethanolic leaf extract of E. californicum was studied for its phytochemical constituents, antioxidant potential, and free radical scavenging activity. Phytochemical analysis revealed the presence of flavonoids, saponins, phenols, tannins, terpenoids, cardiac glycosides, and steroids. The abundance of total phenol (78.58 ± 0.016 μg GAE/mg) and flavonoid content (6.76 ± 0.003 μg QE/mg) and the strong reducing activity in the FRAP assay indicated the antioxidant potential of the leaves. Free radical scavenging activity was confirmed by a dose-dependent response on the DPPH assay (IC50 0.071 mg/mL). Since reactive oxygen species are the main culprits for causing oxidative stress in our body, studying the effect of plant extracts on superoxide, hydrogen peroxide, and hydroxyl radicals found that it has the ability to neutralize all three. IC50 was found to be 0.083 mg/mL for superoxide radicals, 0.033 mg/mL for hydrogen peroxide, and 0.080 mg/mL for hydroxyl radicals. Herein, we report that E. californicum is a potential source of bioactive components with strong radical scavenging activity. This holy herb could serve as a healing agent against oxidative stress and holds promise for the development of nutraceuticals.